The Relationship between Females and Males - Olimjonovna, Komilova Shahnoza; Bekpulatovna, Nunnova Gulshaydo (Journal of Innovation in Education and Social Research, 2025)
The relationship between males and females is a complex and dynamic interaction shaped by biological, psychological and social factors. In today’s fast-paced world, the relationship between males and females is a hot topic in discussion. Members of both genders are trying to build healthy relationship with their partners, however, they are facing the number of problems at the same time.